CRITICAL REALISM IN FRENCH LITERATURE - Makhliyo Atamirzayeva (Galaxy International Interdisciplinary Research Journal, 2021)
Literature of France in the 1830s reflected those new features of the social and cultural development of the country that took shape in it after the July Revolution. Critical realism is becoming the leading trend in French literature. In the 1830-1840s. all significant works of O. Balzac, F. Stendhal, P. Mérimée appear. At this stage, realist writers are united by a common understanding of art, which boils down to an objective reflection of the processes taking place in society. For all their individual differences, they are characterized by a critical attitude towards bourgeois society. In the early stages of the creative development of artists, their close connection with the aesthetics of romanticism (often called "residual romanticism" (The Charterhouse of Parma by Stendhal, Thе Magic Skin by Balzac, Carmen by Merimee) is clearly visible.